What really matters in Code Review? A study about challenges and opportunities related to code review in industry - Cunha, Atacílio Costa; Conte, Tayana; Gadelha, Bruno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
Code review is a widely known process where developers assess each other’s codes. Since the Modern Code Review (MCR) activities bring countless opportunities for the industry, numerous aspects can be evaluated about the result of the MCR on the quality of the software. Based on that, we evaluated the perspective of software practitioners on code review by applying a survey to understand more about the aspects of the MCR in their software development routine and their impressions about how it brings quality to the software. Our results reaffirm that the MCR is seen not only as important but also is associated with the quality of the product. Besides that, we highlight the aspects of the MCR that bring benefits to the software and the development process. We also found results that highlight which aspects of the MCR can negatively impact the product and which factors allow the MCR to be executed properly. This research contributes to expanding the perspective of quality aspects, challenges, and benefits that can be obtained with the MCR process applied in the software development industry.